2002
DOI: 10.1006/qres.2001.2285
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon Dating, Chronologic Framework, and Changes in Accumulation Rates of Holocene Estuarine Sediments from Chesapeake Bay

Abstract: Rapidly accumulating Holocene sediments in estuaries commonly are difficult to sample and date. In Chesapeake Bay, we obtained sediment cores as much as 20 m in length and used numerous radiocarbon ages measured by accelerator mass spectrometry methods to provide the first detailed chronologies of Holocene sediment accumulation in the bay. Carbon in these sediments is a complex mixture of materials from a variety of sources. Analyses of different components of the sediments show that total organic carbon ages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 24 publications
0
61
0
1
Order By: Relevance
“…Perhaps, then, the expansive marshland observed today is a metastable, relict feature that developed under higher sediment supply rates in the past. For example, sedimentation rates in the Chesapeake Bay and Coastal Massachusetts increased 4 to 10 times after European settlement and deforestation (29,30), and marshes of the Plum Island Estuary in Massachusetts were likely restricted to the fringes of an open-water basin until some time after 680 years B.P. (31).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, then, the expansive marshland observed today is a metastable, relict feature that developed under higher sediment supply rates in the past. For example, sedimentation rates in the Chesapeake Bay and Coastal Massachusetts increased 4 to 10 times after European settlement and deforestation (29,30), and marshes of the Plum Island Estuary in Massachusetts were likely restricted to the fringes of an open-water basin until some time after 680 years B.P. (31).…”
Section: Discussionmentioning
confidence: 99%
“…These cores vary in length from 0.5 to 20 m and contain histories of sedimentation rates, organic carbon sources, salinity and temperature regimes, O 2 conditions, and biological changes evidenced in microfossil assemblages and plant seeds over the last 12 000 yr (Colman et al 2002). Time lines have been established in cores using isotopic tracers (e.g.…”
Section: Sediment Record Of Eutrophicationmentioning
confidence: 99%
“…In this study, shell samples have been calibrated using the global average marine reservoir correction (᭝R ϭ0), for the following reasons. First, where recorded, near-zero ␦ 13 C values indicate a marine source of carbon (Colman et al, 2002). Second, while a strong, upwelling-related offset has been identified for the southern Portuguese margin (᭝R ϭ235 Ϯ35 14 C yr) (Soares, 1993), the same study also identified considerable variability between locations including a ᭝R value of 5 Ϯ70 14 C yr at Vila Real de San Antonio at the mouth of the Guadiana and a general reduction in ᭝R prior to 2000 14 C yr.…”
Section: Chronologymentioning
confidence: 99%